Mitochondrial genome insights into the spatio-temporal distribution and genetic diversity of Dendrobium hancockii Rolfe (Orchidaceae) - Hou, Zhenyu; Wang, Mengting; Jiang, Yu; Xue, Qingyun; Liu, Wei; Niu, Zhitao; Ding, Xiaoyu (Frontiers in Plant Science, 2024)
Introduction With its distinctive evolutionary rate and inheritance patterns separate from the nuclear genome, mitochondrial genome analysis has become a prominent focus of current research. Dendrobium hancockii Rolfe, a species of orchid with both medicinal and horticultural value, will benefit from the application of the fully assembled and annotated mitochondrial genome. This will aid in elucidating its phylogenetic relationships, comparative genomics, and population genetic diversity. Methods Based on sequencing results from Illumina combined with PacBio and Nanopore, the mitochondrial genome map of D. hancockii was constructed. Comparative analysis was conducted from the perspectives of phylogeny across multiple species, selection pressure on protein-coding genes, and homologous segments. The population diversity of D. hancockii was analyzed using single nucleotide polymorphism (SNP) data from the mitochondrial genome and single-copy nuclear genes. Results and discussion This research constructed a circular mitochondrial map for D. hancockii, spanning 523,952 bp, containing 40 unique protein-coding genes, 37 transfer RNA genes, and 4 ribosomal RNA genes. Comparative analysis of mitochondrial genes from 26 land plants revealed a conserved gene cluster, "rpl16-ccmFn-rps3-rps19," particularly within the Dendrobium genus. The mitochondrial genome of D. hancockii exhibits a lower point mutation rate but significant structural variation. Analysis of 103 resequencing samples identified 19,101 SNP sites, dividing D. hancockii into two major groups with limited gene flow between them, as supported by population diversity, genetic structure analysis, principal component analysis, and phylogenetic trees. The geographical distribution and genetic differentiation of D. hancockii into two major groups suggest a clear phytogeographical division, likely driven by ancient geological or climatic events. The close alignment of mitochondrial data with nuclear gene data highlights the potential of the mitochondrial genome for future studies on genetic evolution in this species.